Improving laboratory diagnostics in myasthenia gravis. (3rd June 2021) - Gastaldi, Matteo; Scaranzin, Silvia; Businaro, Pietro; Mobilia, Emanuela; Benedetti, Luana; Pesce, Giampaola; Franciotta, Diego
ABSTRACT: Introduction : Myasthenia gravis (MG) is a prototypical autoimmune disease, characterized by pathogenic autoantibodies targeting structures of the neuromuscular junction. Radioimmunoprecipitation assays (RIPAs) represent the gold standard for their detection. However, new methods are emerging to complement, or overcome RIPAs, also with the perspective of eliminating the use of radioactive reagents. Areas covered : We discuss advances in laboratory methods, prompted especially by cell-based assays (CBAs), for the detection of the autoantibodies of MG diagnostics, above all those to the nicotinic acetylcholine receptor (AChR), muscle-specific kinase (MuSK), and low molecular-weight receptor-related low-density lipoprotein-4 (LRP4). Expert opinion : CBA technology makes AChRs aggregate on cell membranes, thus allowing to detect autoantibodies to clustered AChRs, with reduction of seronegative MG cases. The diagnostic relevance of RIPA/CBA-measurable LRP4 antibodies is still unclear, in Caucasian patients at least. Live CBAs for the detection of AChR, MuSK, and LRP4 antibodies might represent an alternative to RIPAs, but first require full validation. CBAs could be used as screening tests, limiting RIPAs for antibody quantification. To this end, ELISAs might be an alternative. Fixation procedures preserving enough degree of antigen conformationality could yield AChR and MuSK CBAs suitable for a wide use in clinical-chemistry laboratories